Small hive beetle, Aethina tumida, situation in africanized honey bees (Apis mellifera) colonies in Costa Rica: Sampling of apiaries 2014-2017 - Ramírez, Marianyela (2018)
The first report of the small hive beetle, Aethina tumida, in Central America was in El Salvador in 2013 and in Nicaragua in 2014, which increases the risk of invasion of this pest into Costa Rica. Therefore 359 colonies belonging to 62 apiaries located in the provinces of Guanacaste, Puntarenas, Alajuela, San José and Heredia, were sampled from June 2014 to September 2017. Observations of the brood and the adult bees were performed. Furthermore, two Cutts Beetle Blaster® traps were placed per colony, per eight to fifteen days. The traps were analyzed at the Bee Pathology Lab of CINAT-UNA. The presence of the small hive beetle was only confirmed at the sentinel apiary located in La Cruz-Guanacaste, in August 2015. Therefore, the presence of A. tumida is confirmed in africanized honey bee colonies in Costa Rica, with a limited distribution to La Cruz-Guanacaste. Due to the flight capacity of adult beetles and the movement of the colonies by the beekeepers, we recommended to continue the sampling of the apiaries, because the negative situation could change.